Prevention of the inhibitory effect of intraperitoneal 5-FU on intestinal anastomosis by zinc - Ali Rıza TÜMER; Nuri Aydın KAMA; Sevda F. MÜFTÜOĞLU; Cenap DENER; Leyla TÜMER; Atilla DAĞDEVİREN (Turkish Journal of Gastroenterology, 2019)
-